Pokémon adventures. Volume 10, Gold & Silver - Kusaka, Hidenori (VIZ Media, 2010)
In order to assist Professor Oak's research, a young Trainer, Crystal, hits the streets of Cherrygrove City with a new Pokédex in hand! Her goal is to catch all kinds of Pokémon! And what will happen when the Legendary Pokémon Suicune has awakened?!--P. [1] of cover.